(untitled) (Marketing Journal, 2025)
This article highlights the theoretical and practical aspects of managing the innovation potential of food industry enterprises within the context of regional economic development . The study substantiates that the food industry is one of the key sectors of the regional economy , and its innovation activity directly affects regional competitiveness , employment , and the growth of added value . The mechanisms for managing innovation potential are analyzed in terms of their structural components , including the institutional environment , financial incentives , technological modernization , human capital , and the coherence of managerial decisions . Additionally , the article assesses the effectiveness of support tools for food industry enterprises in implementing innovation policy at the regional level . The research results serve as a scientific and practical foundation for developing regional development strategies and improving innovation management mechanisms in the food industry .